EXPLANATION THROUGH THE MEDIA OF CULTURAL FIGURE BAYAN (WETUTELU) ON KNOWLEDGE OF MOTHERS TO CHILDREN ABOUT BALANCED NUTRITION MESSAGES - Suwidari Fine; AASP Chandradewi; Lalu Khairul Abdi; Yuli Laraeni; I Gde Narda Widiada (Poltekkes Kemenkes Mataram, 2022)
Background: One of the efforts to overcome nutritional problems is to increase knowledge about nutrition through nutrition counseling. Learning can be influenced by education. People with higher education tend to have a broader understanding and an openness to accept new things. Meanwhile, someone with low education tends to have old thinking patterns and is less open to new things, including powerful areas in holding their customs. One way to influence the community's mindset in such conditions is to use a trusted communication facilitator who can be a role model for the community. So that in this study, the role of traditional leaders is used so that the community is more receptive to the material presented. Objective: To determine the effect of counseling through the media of Wetu Telu Bayan traditional leaders on the knowledge of mothers of children under five about the message of balanced nutrition. Methods: This research is a pre-experimental study that allows testing the changes after the intervention. The research design used is a one-group pre-test-post-test design. Result: An increase in knowledge scores in the form of differences in scores from pretest to post-test. Analysis using Wilcoxon regarding the effect of counseling on balanced nutrition messages by traditional leaders on the knowledge of mothers of children under five, the results were p = 0.00 or p <0.05, meaning that there was an effect. Conclusion: There is an effect of counseling through the media of Wetu Telu Bayan traditional leaders on the knowledge of mothers of children under five about the message of balanced nutrition.